The influence of the vegetative stage of Galega orientalis on the quality of haylage prepared from it - Starkovskiy Boris; Simonov Gennadiy; Malinovskaya Yuliya; Simonov Aleksandr (E3S Web of Conferences, 2020)
Studying the effect of plant raw materials on the quality of the finished haylage made of Galega orientalis when preparing it at different vegetative stages of plants. Special attention is paid to haylage in the livestock ration structure because compared to silage it has higher nutritive value and contains more dry matter, protein, sugars, macro- and microelements, as well as biologically active substances. It is worth to note that haylage rations have a beneficial impact on the animal body and the productivity of animals, which, in turn, reduces production costs. it has been proved that the green mass of Galega orientalis is a good raw material for making haylage if the technological requirements for feed preparation are met.